2021
DOI: 10.18502/ijph.v50i5.6113
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MALAT1 Promote Cell Proliferation and Invasion by sponging miR-125b to Modulate HMGA1 Expression in Laryngocarcinoma

Abstract: Background: Laryngocarcinoma is the most frequent head and neck malignant tumor. MALAT1 have a role in promoting cell proliferation and metastasis in several tumors. This research aimed to investigate the great roles of MALAT1in laryngocarcinoma. Methods: Overall, 54 cases of laryngocarcinoma tissues pathological specimens and paracancerous tissues were collected by surgical resection from the Department of Otolaryngology-Head and Neck Surgery at the Shandong Provincial Hospital affiliated to Shandong Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Unlike linear RNA with a 5′ cap and a 3′ poly (A) tail at the end, circRNA is characterized by a covalently closed loop structure, which has neither 5′ to 3′ polarity nor a polyadenylated tail, and is highly resistant to exonucleases, so it has high stability and shows tissue-specific expression. Studies have shown that dysfunctional and aberrant circRNA expression is also associated with malignancy [ 11 , 12 ]. Therefore, circRNA is likely to become a potential biomarker for tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike linear RNA with a 5′ cap and a 3′ poly (A) tail at the end, circRNA is characterized by a covalently closed loop structure, which has neither 5′ to 3′ polarity nor a polyadenylated tail, and is highly resistant to exonucleases, so it has high stability and shows tissue-specific expression. Studies have shown that dysfunctional and aberrant circRNA expression is also associated with malignancy [ 11 , 12 ]. Therefore, circRNA is likely to become a potential biomarker for tumors.…”
Section: Introductionmentioning
confidence: 99%
“…MALAT1 is highly expressed in mice with acute viral myocarditis, and knockdown of MALAT1 attenuates Th17-related responses, such as the expression of IL-17-related pro-inflammatory factors [26]. The relationship between IL- regulates cell proliferation through miR-125b [30,31], and the expression of miRNA-125b is down-regulated in psoriasis patients [14,16]. Finally, we verified the expression of the MALAT1/miR-125b/BRD4 signaling axis.…”
Section: Discussionmentioning
confidence: 62%
“…Literature search on “lncRNA-miRNA pairs” in cancer revealed one lncRNA (MALAT1) -miR125b interaction in laryngocarcinoma ( Zong et al, 2021 ), three lncRNA (TUG1, NEAT1, MALAT1) -miR-34a interactions reported in endometrial cancer, Nasopharyngeal Cancer, Melanoma ( Liu et al, 2017 ; Ji et al, 2019 ; Li et al, 2019 ) and three lncRNA (PVT1, NEAT1, and MALAT1) -miR-30a-5p interactions in papillary thyroid carcinoma, gastric cancer, Hepatocellular Carcinoma ( Feng et al, 2018 ; Pan et al, 2018 ; Rao et al, 2021 ). Previous studies revealed that the lncRNAs H19 and NEAT1 were found to directly target miR-193a-3p in Hepatocellular Carcinoma and Lung Adenocarcinoma, respectively ( Ma et al, 2018 ; Xiong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%